2002
DOI: 10.1046/j.1529-8027.2002.02004.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggravated reperfusion injury in STZ‐diabetic nerve

Abstract: The streptozocin (STZ)-diabetic nerve manifests increased morphological susceptibility to a superimposed acute ischemic injury, and reperfusion injury exaggerates ischemic nerve pathology. To determine whether STZ-diabetic nerves are susceptible to reperfusion, we evaluated the pathological consequences after 2.5 hours of ischemia followed by 3 and 24 hours of reperfusion in a 20-week STZ-diabetic rat sciatic nerve. After 3 hours of reperfusion, endoneurial edema developed in diabetic nerves, whereas non-diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…Previous studies have demonstrated that ischemia to nerve can cause fiber degeneration, and reperfusion following ischemia causes additional fiber degeneration, mediated by an inflammatory response and oxidative stress [2,3]. The current finding of less edema and fiber degeneration in sciatic but not in tibial nerve is consonant with our previous studies that demonstrate that neuroprotection, whether with hypothermia or antioxidants, occurs when the ischemic insult is moderate (sciatic nerve) but fails when the insult is extreme [11,12,15,16].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies have demonstrated that ischemia to nerve can cause fiber degeneration, and reperfusion following ischemia causes additional fiber degeneration, mediated by an inflammatory response and oxidative stress [2,3]. The current finding of less edema and fiber degeneration in sciatic but not in tibial nerve is consonant with our previous studies that demonstrate that neuroprotection, whether with hypothermia or antioxidants, occurs when the ischemic insult is moderate (sciatic nerve) but fails when the insult is extreme [11,12,15,16].…”
Section: Discussionsupporting
confidence: 87%
“…Reperfusion following ischemia (IR) results in additional fiber degeneration, and mechanisms of reperfusion injury have been postulated to be due to the additional insult of inflammatory response [2] and oxidative injury [3]. The pro-inflammatory cytokines, especially tumor necrosis factor-alpha (TNF-α), is a major component of the inflammatory response following IR injury and is rapidly upregulated from mRNA level to protein level [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These alterations are known to be exaggerated in diabetic neuropathy [15]. In our previous study, we demonstrated that reperfusion following ischemia results in excessive axonal degeneration [3] and apoptosis of SC [6,7] in 1-month and 4-month diabetic peripheral nerve when compared with normal nerves subjected to the identical insult.…”
Section: Discussionmentioning
confidence: 83%
“…Reperfusion amplifies physiological and pathological abnormalities in ischemic nerves of normal rat [10] and exaggerates the ischemia pathology in a 20-week STZ-diabetic rat sciatic nerve after 2.5 h of ischemia followed by 3 and 24 h of reperfusion [11].…”
Section: Introductionmentioning
confidence: 97%